Penerapan Web untuk Pengolahan Data Pegawai Kantor Desa Menggunakan Bahasa Pemrograman PHP dan UML - Lase, Dewantoro; Alasi, Tomy Satria (Universitas Sari Mutiara Indonesia Medan, 2024)
The Village Office is the center of government and public services in the village as well as a place where residents interact with the village head and his apparatus. At the Bandar Setia Village Office, the process of processing employee data is currently still using a semi-computerized system (using the Microsoft Excel 2007 application), so to view the data of an employee must be viewed vertically. This makes it difficult to see the whole information about an employee. The process carried out seems very slow and ineffective and efficient. In solving this problem, the author designed a Web-Based Employee Data Processing Information System which aims to simplify the process of processing employee data and accelerate the presentation of the required information and reduce errors in employee data processing, in this study the employees tested were around three employees and the results were no errors. In this design, the author uses PHP Programming Language, and MySql database and Adobe Dreamweaver CS6 Application.